Peran Pengendalian Internal Internal dalam Memoderasi Hubungan Solvabilitas dan Likuiditas terhadap Audit Delay - Sarah Shaqila; Nurkholis Nurkholis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the effect of solvency and liquidity on audit delay and to examine the role of internal control as a moderating variable in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2024 period. Timely audited financial statements are essential for ensuring transparency, supporting investment decisions, and maintaining stakeholder confidence. This research employed a quantitative approach using secondary data obtained from companies’ annual financial reports. The sampling technique used was purposive sampling, resulting in 18 companies with a total of 126 observations. Data were analyzed using Moderated Regression Analysis to evaluate both direct and moderating effects. The results show that solvency has a positive and significant effect on audit delay, while liquidity has no significant effect on audit delay. Internal control moderates the effect of solvency on audit delay by weakening the relationship but does not moderate the effect of liquidity. Simultaneously, solvency, liquidity, and internal control significantly affect audit delay. These findings indicate that firms’ financial conditions and effective internal control contribute to the timely completion of audits and improve the quality of financial reporting.